Comparison of conventional light-framed wood construction and structural insulated panels - Ledford, Bradley T. (Kansas State University, 2010)
Conventional wood framing, also known as stick framing, has been around for hundreds of years. It is an easy, effective method for building new houses and small commercial projects. However, it may no longer the best option for new construction. The development of Structural Insulated Panels (SIPs) began over 70 years ago at the United States Forest Products Laboratory in Wisconsin. Scientists believed that plywood sheathing alone could provide adequate strength to support the loads a structure encounters. Over the years, SIPs have evolved to what they are today: a rigid insulation foam core sandwiched between two skins, often made of oriented strand boards (OSB). Compared to stick framing, SIPs are faster to erect in the field and also provide more strength to resist most loads; they are better with axial and transverse loads. Stick framing can be built more robust to resist in-plane shear loads. The quality of the material of SIPs also means better quality construction. The insulating values SIPs provide are far superior to that of fiberglass insulation used in stick framing, saving money for the owner as well as energy from natural resources. Not only do they provide better thermal protection, but they are also better for the environment because of manufacturing processes and construction practices. When it comes to other issues such as fire, smoke, termites, and ventilation, SIPs are no worse than stick framing. SIPs follow the same steps for construction used in stick framing with, perhaps a little more care needed to insure proper ventilation. SIPs have proven themselves in the laboratory and in the real world. SIPs should be considered more often as an option, replacing stick framing for the major structure elements and insulation for new buildings.
Keywords: Structural insulated panels; Architecture (0729)